PENERAPAN METODE PEMBELAJARAN GALLERY WALK UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN HIDROKARBON DAN MINYAK BUMI DI KELAS XI SMA NEGERI 1 TAPUNG HULU - Rhizky Okta Defira; Rini '; Elva Yasmi Amran (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research was conducted because of the law learning achivement of student on the Hydrocarbon and Petroleum subject who has not reached KKM was 70,00 that has been establishted in school. The research aimed to improve learning achievement of students on Hydrocarbon and Petroleum subject in XI class MIA SMAN 1 Tapung Hulu. This research was a kind of experimental research with pretest-posttest design. The research was conducted in SMAN 1 Tapung Hulu. The samples of this research were the students of XI MIA 4 class, as the experimental class and students of XI MIA 3 class, as the control class, which were determined randomly after doing the normality test and homogeneity test. The learning process at experimental class and control class used scientific approach which was based on the curriculum in 2013. Experimental was the class which was given the treatment that used gallery walk method, while the control class was not. The data analysis technique we used is the t test. Criteria testing H0 accepted if tcount>ttable, dk=n1+n2-2 with α=0,05. Based on the result of data analysis test, we obtained tcount>ttable is 3,79 >1,67,it meant that the application of gallery walk of leraning method could improve learning achievement on the Hydrocarbon and Petroleum subject in XI classs SMAN 1 Tapung Hulu.Key Words : Gallery Walk Learning, Learning Achievement, Hidrocarbon and Petroleum